Learning the hard way? Adapting to climate risk in Tanzania - Sofie Waage Skjeflo; Nina Bruvik Westberg (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2014)
We use recent panel data on Tanzanian farm households to investigate how previous exposure to weather shocks affects the impact of a current shock. Specifically, we investigate the impact of droughts on agricultural outcomes and investments in children's health, measured by their short- and long-term nutritional status. As expected, we find that droughts negatively impact yields, and more so the more severe the drought is. We also find suggestive evidence that the more shocks a household has experienced in the past, the less crop yields are affected by a current shock. This suggests that households are able to learn from their past shock experience, and could imply that households are able to adapt to climate risk. Our results also suggest that the impact of a shock depends on when the household last experienced a shock. In terms of child health, our preliminary results are unable to uncover any clear shock impact on the short-term nutritional status of children, however long-term nutritional outcomes are negatively affected by past shocks. Further analyses using more recent weather data is necessary in order to conclude.
Keywords: I12; I13; Q12; Q54; 330; Climate risk; income shocks; adaptation; child health; Tanzania